Can Digital Transformation Reduce Government Corruption? A Meta-Analysis - Munshi, Munshi; Manni, Umme Humayara (PT Mattawang Mediatama Solution, 2025)
This meta-analysis examines the potential of digital transformation in reducing government corruption by synthesizing findings from 17 empirical studies published in the last five years. Using the PRISMA protocol, a comprehensive literature search was conducted, and studies were screened for eligibility. The meta-analysis revealed a substantial negative correlation between corruption and digitalization/e-government, with an overall effect size of -0.93 (95% CI: -1.18 to -0.68) based on the Random Effects Model. The results suggest that higher levels of digital transformation are associated with lower levels of corruption. However, the study also highlights the complex and context-dependent nature of this relationship, as cultural, economic, and institutional factors can moderate the impact of digitalization on corruption. The findings underscore the importance of investing in digital infrastructure, promoting digital literacy, and fostering ethical governance practices to effectively combat corruption through digital transformation.